Local Wisdom-Based Education: Implementation of Gus Dur's Ideas in Schools - Tobi, Tobi; Bakar, M. Yunus Abu; Mas'ud, Ali (Maharot : Journal of Islamic Education, 2025)
This study aims to identify and analyze the implementation of education based on local wisdom as well as the humanistic and inclusive values of Gus Dur in secondary schools. The research employs a qualitative approach using field research methods. Data was collected through classroom observations, in-depth interviews with teachers, principals, and students, as well as documentation of activities rooted in local culture. Data analysis was conducted through data reduction, data display, and conclusion drawing/verification. The findings indicate that the integration of local wisdom in schools is achieved through the reinforcement of communal cooperation, the practice of local cultural traditions, and contextualized learning. Meanwhile, the implementation of Gus Dur's values is evident in the development of an inclusive school culture, interfaith dialogue, and character-strengthening activities such as deliberation forums, tolerance initiatives, and the cultivation of humanistic attitudes. The study concludes that the integration of local wisdom and Gus Dur’s values fosters a pluralistic and humanistic learning environment that shapes students’ adaptive and diversity-oriented character.